REDESIGNING TROLLEY JACK TO BE MORE EFFICIENT, CONVENIENT AND SAFE - Haidon, Mohd Akmal Hadi Bin; Guntabid, Donny; Gemuru, Lasius; Solimin, Niel; Liew, Freadoline Fook; Idek, Sirhajwan (MATTER: International Journal of Science and Technology, 2020)
This research examined the efficiency of a specifically modified trolley jack in extracting car components particularly gearbox and transferring these components to a specific workspace. This project was built to minimize physical workload, reduce the time taken to perform this task, and mitigate health and safety risks. There were 20 respondents involved in this study and they were required to test the project before completing observation checklists and questionnaires. The findings revealed that the students had strong approval on each function and feature of the project. There were a few recommendations on how the project could be improved to be safer and more efficient.